An Experimental Study of the Effects of Temperature and Acceleration on Gear Rattle Noise - Bozca, Mehmet (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract This study aimed to experimentally investigate the effects of temperature and acceleration on gear rattle noise in an automotive transmission. For this aim, gear rattle noise was measured at different temperatures depending on the acceleration of the gear motion. Thus, gear rattle noise variations were presented for each speed of the gearbox at different temperature conditions. The gear rattle noise calculated by empirical formulas and the experimentally obtained gear rattle noise were compared for each speed of the gearbox. It was observed that gear rattle noise increases with the acceleration of the gear motion. Furthermore, increasing the temperature causes an increase in gear rattle noise. By accurately estimating the temperature effect on gear rattle noise and by selecting an appropriate lubricant, it is possible to reduce rattle noise in the gearbox in an automotive transmission.